Kepemimpinan Demokratis Kepala Sekolah dalam Pemanfaatan Ruang GTK untuk Mengembangkan Profesionalisme Guru SD Langensari 03: The Principal's Democratic Leadership in Utilizing the Staff and Teacher Room to Develop the Professionalism of Teachers at SD Langensari 03 - Rina Ardani; Senowarsito Senowarsito; Rosalina Br Ginting (ITScience (Information Technology and Science), 2026)
This study is motivated by the importance of developing teacher professionalism in the digital era through the utilization of